Morphological Characterization and Antioxidant Activity of Actinobacteria from Xylocarpus granatum Growing in Mangrove Habitat - Ratte, Marina; Batubara, Irmanida; Lestari, Yulin (Universitas Brawijaya, 2022)
Xylocarpus granatum produces various bioactive compounds with diverse biological activities, one of them as an antioxidant. Endophytic actinobacteria can also produce bioactive compounds. This study aimed to explore the existence of the endophytic actinobacteria of X. Granatum and determine its antioxidant activity. The research method begins with the isolation of endophytic actinobacteria from fruits, seeds, and leaves using selective media Humic Acid (HV). Furthermore, characterizing the obtained isolates using four different media, namely YSA, ISP2, ISP3, and ISP4, measured antioxidant activity for actinobacterial supernatants and actinobacterial ethyl acetate extracts using the DPPH method. The results showed that from X. granatum, 15 isolates of endophytic actinobacteria were obtained from fruit, seeds, and leaf. Endophytic actinobacteria isolates from X. granatum showed different colors of aerial mycelium, substrate mycelium, and spore chain type. XGF11, XGF12, and XGF4 isolates produced high antioxidant activity of the supernatant; 57.30%, 49.77%, and 41.90% inhibition, respectively. The antioxidant capacity of XGF12 ethyl acetate extract was 501.60 Î¼g AEAC/mg extract and 465.47 Î¼g AEAC/mg extract for XGF11 ethyl acetate extract. DNA extraction and 16S rRNA amplification from endophytic actinobacteria X. granatum according to Presto Mini gDNA Bacteria Kit Protocol. Based on 16S rDNA gene analysis, isolates XGF12 and XGF11 showed 99.16% and 99.42% similarities with Streptomyces xylanilyticus, respectively. Meanwhile, XGF4 showed to have 99.82% similarities with Brevibacterium sediminis.